Non-gouty arthritis in sickle cell disease: report of 37 consecutive cases. Issue 4 (August 1984) - de Ceulaer, K; Forbes, M; Roper, D; Serjeant, G R
Abstract : Arthritis in association with sickle cell disease was seen in 37 patients in a 21/2-year period. Cases of gout and of avascular necrosis of the femoral head were excluded. In 12 patients a non-inflammatory effusion occurred during the course of a painful crisis, in 12 patients an ankle effusion occurred in association with spontaneous development or deterioration of leg ulceration, and in 13 patients there was a group of miscellaneous arthritides. Ankle arthritis with leg ulceration has not been previously recognised, and its association with spontaneous ulceration, which is presumed to have a vaso-occlusive origin, is compatible with ischaemic synovial damage. The aetiology may therefore be similar to that believed to account for effusions in association with the painful crisis.